Congruences on ternary semigroups - Chronowski, A. (Ukrains’kyi Matematychnyi Zhurnal, 2004)
We study ternary semigroups as universal algebras with one associative operation. We investigate their algebraic structure and associated representations. Results for congruences of ternary semigroups generated by binary relations are presented.